Pemetaan Jenis, Indikator dan Kegunaan Kepemimpinan Pendidikan: Kajian Literatur dari Situs Indonesian Publication Index (IPI) - Hidayat, Rais; Patras, Yuyun Elizabeth (Universitas Kristen Satya Wacana, 2018)
The site of Indonesian Publication Index (IPI) has become a benchmark and reference research in Indonesia. The purpose of this research is to map educational leadership articles on IPI sites based on types, indicators, and usefulness of educational leadership. This research method used literatur study, where researchers examined 91 scientific articles sourced from the corpus of the IPI database, researchers do the sorting and analysis and then the data communicated through descriptive statistics. The findings of this research are as follows: (1) types of educational leadership research methods include qualitative and quantitative methods, but the types of mixed methods are rarely found; (2) types of publicized educational leadership research are in accordance with existing educational leadership theories, but Indonesia has several characteristics of educational leaders such as boarding school leadership; (3) researchers in Indonesia have used indicators of effective educational leadership in accordance with what researchers use in other countries; and (4) education leadership researchers in Indonesia have provided recommendations for improving educational leadership. The above findings are expected to be discussed in developing educational leadership research in Indonesia.